Implementing Pro Poor Budgeting in Poverty Reduction: A Case of Local Government in Bone District, South Sulawesi Province, Indonesia - Nursini, Nursini; Agussalim, Agussalim; Suhab, Sultan; Tawakkal, Tawakkal (International Journal of Economics and Financial Issues, 2018)
The number of transfer funds managed by local governments has increased significantly but the decline of the poor is quite slow. The implementation of pro poor budgeting depends on the extent to which local governments formulate program planning and budgeting related to poverty alleviation. This study uses descriptive analysis approach and contents analysis on planning documents and local budgets to know the number of programs and the amount of government spending related to poverty reduction in Bone District. The study finds that the number of programs implemented by Bone District governments in 2015 amounted to 45 programs with budget realization of IDR 126.2 billion. This figure is relatively small only 6.86 percent of IDR 1841.8 billion total local government spending in Bone District. This study suggests the need for an increasing the number of programs and the proportion of spending associated with poverty alleviation. Keywords: Pro-poor budgeting, poverty, fiscal decentralization JEL Classifications: H7, O1, O2